Student Perspective: Margaret Chase Smith Library 2011 Essay Contest: - Anderson, Zoe; Clift, Ali; Murphy, Allaina (Maine Policy Review, 2012)
Each year, the Margaret Chase Smith Library sponsors an essay contest for Maine high school seniors. The focus of the 2011 contest was environmental protection. The essay prompt quoted a 1972 statement from Sen. Smith: “We must recognize that we’re not going to eliminate pollution overnight. It’s going to be a hard, long fight. It’s going to take a long time and a lot of sacrifice on the part of each one of us.” By happy coincidence, the essay contest topic fits perfectly with the subject matter of this special issue of Maine Policy Review on sustainability. We feature here the three 2011 prize-winning essays, which draw upon contemporary and historical examples along with the personal experiences and opinions of these talented young people.